2011
DOI: 10.4172/jndt.1000101
|View full text |Cite
|
Sign up to set email alerts
|

Immune Alterations in Liver Cirrhosis: Its Relationship with Etiology,Child Pugh Stage and Malnutrition

Abstract: Background: Immune alterations in liver cirrhosis are variable and only a few have been correlated with the severity of the disease, malnutrition or its etiology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…People who drink minimal amounts of alcohol are at a risk of causing non-alcoholic fatty liver disease, characterized by the accumulation of fat in the liver [13]. Risk factors for developing nonalcoholic fatty liver disease are high cholesterol and high triglycerides, which develop from a high intake of saturated fat, trans fat, sugar and cholesterol, all of which are found in junk foods [14,15]. Malnutrition is also a risk factor for non-alcoholic fatty liver disease.…”
Section: Health Consequences Of Junk Food Consumptionmentioning
confidence: 99%
“…People who drink minimal amounts of alcohol are at a risk of causing non-alcoholic fatty liver disease, characterized by the accumulation of fat in the liver [13]. Risk factors for developing nonalcoholic fatty liver disease are high cholesterol and high triglycerides, which develop from a high intake of saturated fat, trans fat, sugar and cholesterol, all of which are found in junk foods [14,15]. Malnutrition is also a risk factor for non-alcoholic fatty liver disease.…”
Section: Health Consequences Of Junk Food Consumptionmentioning
confidence: 99%
“…Lower complement levels were closely correlated with liver injury and impaired liver aggregation (Zhang, et al, 2016). Castellanos et al (2011) found that C3 and C4 complements decreased significantly in cirrhotic patients. They suggested that the reduction by alternative pathway can be the result of an increased consumption or a decreased production due to liver insufficiency.…”
Section: Disscussionmentioning
confidence: 99%
“…Liver is the main metabolizing organ in the body [44]. It is mainly responsible for the immunologic equilibrium hence any disturbance in its function will compromise the immune state [45]. Treatment of HIV infection with highly antiretroviral therapy (HAART) may be limited by liver toxicity [46].…”
Section: Liver Disordersmentioning
confidence: 99%